THE PARADIGM OF THE POLITICAL FARSIGHTEDNESS OF THE KAZAKH BI-SPEAKERS - Д.C., Рaев; А.Ж., Тоқмұрзaевa (Journal of Oriental Studies, 2019)
In this article we make an approach to the scientific and theoretical analysis of the paradigm of political foresight of biys of the Kazakh khanate of the ХҮІІ-ХҮІІІ centuries in relation to the diplomatic system of international relations. In the scientific-theoretical and methodological approach to this issue, first of all, it should be taken into account that the Kazakh Biу at any time have personal qualities, having knowledge and skills. It is also said about the political foresight of the Kazakh biys-speakers, predicting the future. Key words: diplomacy, biy-speakers, political foresight, international relations.